Genetic Evaluations of Stillbirth for Five United States Dairy Breeds: A Data-Resource Feasibility Study - Sigdel, Anil; Wu, Xiao-Lin; Parker Gaddis, Kristen L.; Norman, H. Duane; Carrillo, José A.; Burchard, Javier; Peñagaricano, Francisco; Dürr, João (Frontiers in Genetics, 2022)
Genetic selection has been an effective strategy to improve calving traits including stillbirth in dairy cattle. The primary objectives of the present study were to characterize stillbirth data and determine the feasibility of implementing routine genetic evaluations of stillbirth in five non-Holstein dairy breeds, namely Ayrshire, Guernsey, Milking Shorthorn, Brown Swiss, and Jersey. An updated sire-maternal grandsire threshold model was used to estimate genetic parameters and genetic values for stillbirth. Stillbirth data with the birth years of dams from 1995 to 2018 were extracted from the US national calving ease database maintained by the Council on Dairy Cattle Breeding. The extracted stillbirth records varied drastically among the five dairy breeds. There were approximately 486K stillbirth records for Jersey and more than 80K stillbirth records for Brown Swiss. The direct and maternal heritability estimates of stillbirth were 6.0% (4.5 – 7.6%) and 4.7% (3.3 – 6.1%) in Jersey and 6.8% (3.2 to 10.5%) and 1.1% (0.6 to 2.9%) in Brown Swiss. The estimated genetic correlations between direct and maternal genetic effects for stillbirth were -0.15 (-0.38 to -0.08) in Jersey and -0.35 (-0.47 to -0.12) in Brown Swiss. The estimated genetic parameters for stillbirth in these two breeds were within close ranges of previous studies. The reliabilities of predicted transmitting abilities in Jersey and Brown Swiss increased substantially, thanks to the substantial increase in available stillbirth data in the past ten years. The stillbirth records for Ayrshire, Guernsey, and Milking Shorthorn, which ranged approximately between 3K and 12K, are insufficient to implement reliable routine genetic evaluations of stillbirth in these three dairy breeds. Estimated genetic (co)variances and genetic values deviated considerably from the reported ranges of previous studies, and the reliabilities of predicted transmitting abilities were low in these three breeds. In conclusion, routine genetic evaluations of stillbirth are feasible in Brown Swiss and Jersey. However, reliable genetic evaluations of stillbirth in Ayrshire, Guernsey and Milking Shorthorn require further data collection on stillbirth.